LOS ESTUDIOS DE POSGRADO SOBRE DESARROLLO, ORDENAMIENTO TERRITORIAL Y PLANIFICACIÓN URBANA EN EL PERÚ: ¿ENTRE LOS PARADIGMAS DE LA COMPLEJIDAD Y DE LA SOSTENIBILIDAD? - Castillo García, Rodolfo Francisco (2019)
The aim of the present article is do some reflections of the postgraduate studies in Peru about development, territorial classification and urban planning, and on its necessary enrichment or rethinking in the perspective of the paradigms of the «complexity» and of the «sustainability».